2014
DOI: 10.1007/s00381-014-2458-8
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal development of Blake’s pouch cyst: a case report and new insight for its pathogenesis

Abstract: Blake's pouch cyst (BPC), a rare cystic malformation in the posterior fossa, is believed to be caused by the congenital expansion of the posterior membranous area that normally regresses during embryogenesis. However, due to the wide spectrum of the onset pattern and age of patients, the natural history and the pathogenesis are poorly understood. The authors describe the case of a girl who admitted with headache and right abducens nerve paresis at the age of 3 years and 10 months. Magnetic resonance (MR) imagi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 10 publications
(21 reference statements)
0
6
0
Order By: Relevance
“…Hirono reported a child case of BPC that was not present at 8 months and appeared at age of 3 years, suggesting the presence of secondary BPC. [ 7 ] In this case, the BPC was manifested due to a brain tumor, which disseminated ventricle wall widely and obstructed the CSF. However, as many case reports, including our case, the late manifestation of BPC remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Hirono reported a child case of BPC that was not present at 8 months and appeared at age of 3 years, suggesting the presence of secondary BPC. [ 7 ] In this case, the BPC was manifested due to a brain tumor, which disseminated ventricle wall widely and obstructed the CSF. However, as many case reports, including our case, the late manifestation of BPC remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Hirono et al reported a case of postnatal development of hydrocephalus with BPC in conjunction with pilomyxoid astrocytoma, despite the presence of normal neuroimaging twice beforehand. 13 Still, the possibility of postnatal re-expansion of BPC cannot exclude hydrocephalus developing from continued nusinersen administration. The exact effect of nusinersen related to changes in CSF dynamics has not been well described, partly because it is a relatively new drug and has been used only in a small number of SMA patients.…”
Section: Discussionmentioning
confidence: 99%
“…These authors found a hard membrane in the prepontine cistern and confirmed pulsatile movement of the third ventricular floor after perforating this membrane. Hirono et al 7) described a 3-year-old girl with BPC-associated hydrocephalus suffering from headaches and nausea. ETV was initially performed, but the patient developed bacterial meningitis and secondary hydrocephalus, which necessitated a VPS 1 month after the ETV.…”
Section: Discussionmentioning
confidence: 99%
“…2,3) Although the pathophysiology and optimal treatment for hydrocephalus with BPC remains controversial, shunt placement, endoscopic third ventriculostomy (ETV), and fenestration of the cyst have been previously reported. 2,[4][5][6][7][8][9] ETV has been reported to be effective in pediatric patients with BPCassociated hydrocephalus in recent years. 4,6,10) In line with the current trend of using minimally invasive procedures in neurosurgery, ETV is considered a good alternative for hydrocephalus with BPC.…”
Section: Introductionmentioning
confidence: 99%